Diversit#xE9; ethnoculturelle des employ#xE9;s et performance financi#xE8;re des PME camerounaises (Global Journal of Management and Business Research, 2020)
The aim of this paper is to study the influence of employees ethno cultural factors on the financial performance of Cameroonian SMEs. To do this, we evaluated the ethno cultural diversity of employees, first by the customs of the employees ethnic groups which are measured by beliefs, rites, taboos and secondly by the employees ethnic language which is measured by the cognitive capacities of languages. employees. Financial performance is understood by the return on assets (ROA), the return on investments (ROI), the solvency, the evolution of profits and the evolution of liquidity. A multiple linear regression mobilized using the responses collected on 42 SMEs allowed to conclude that only the customs of the ethnic groups of the employees have positive effects on their financial performance.
Keywords: customs; language; financial performance